Contribution of facilities to the success of university sports - benredjem, idriss (sports creativity, 2025)
The study aimed in its general form to know the extent of the contribution of sports facilities management to the success of university sports activities, where we addressed in the first objective the means and structural sports capabilities that may contribute to the development of university sports, while the second objective was about the modern legal and legislative texts that govern and organize university sports, as well as presenting some previous studies similar to the subject of our research, as well as proposing some future visions that may contribute to the success of university sports, as well as coming up with some titles of future studies and hypotheses that need studies by students and specialists in this field